Civic patriotism in the context of solidarity practicesin western european countries - Murzinov, V L.; Murzinov, P V.; Murzinov, Yu V.; Buyanov, V I.; Popov, V A. (International Journal of Engineering and Technology, 2018)
The paper links civil patriotism in the context of solidarity practices to citizensâ€™ civil activity and moral responsibility to a civil community. In the epoch of early modernity, there were such types of civil patriotism as liberal and revolutionary patriotism and national patriotism in Western European countries. In the epoch of late modernity, liberal civil patriotism prevails in the Western democratic countries. It involves a historical and cultural model of civil patriotism and a model of constitutional patriotism with a political dimension.Â
Keywords: Patriotism; Civil Patriotism; Liberal and Revolutionary Patriotism; National Patriotism; Constitutional Patriotism; Western European Countries.